Disabling discourses and human rights law: a case study based on the implementation of the UN Convention on the Rights of People with Disabilities. Issue 1 (2nd January 2016) - Liasidou, Anastasia
Abstract : This article examines the symbolic power of language to construct and convey disabling discourses, albeit ample rhetoric, on the need to reinstate and safeguard disabled people's human rights and entitlements. The role of language and its discursive ramifications need to be explored and problematized in the light of legal mandates and antidiscrimination legislation to abolish stigmatizing and exclusionary regimes on the grounds of disability. Such a critical engagement necessitates a reflective knowledge and constant interrogation of the ways in which language is implicated in power interplays to construct meanings and to legitimize/conceal existing power inequities. The article uses critical discourse analysis in order to discuss the role of language in the construction, sustenance, and dissemination of disabling discourses, taking as an example the First Report of Cyprus on the Implementation of the UN Convention on the Rights of People with Disabilities.